2012
DOI: 10.1111/j.1755-0998.2012.03129.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding in native plants of the Labiatae (Lamiaceae) family from Chios Island (Greece) and the adjacent Çeşme‐Karaburun Peninsula (Turkey)

Abstract: The plant family Labiatae (Lamiaceae) is known for its fine medicinal and aromatic herbs like lavender, mint, oregano, sage and thyme and is a rich source of essential oils for the food, pharmaceutical and cosmetic industry. Besides its great economic importance, the Labiatae family contributes significantly to the endemic flora of Greece and Turkey. Owing to its economic and biological significance and to the difficult identification based on morphological characters of several of its taxa, the Labiatae famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 66 publications
5
75
1
4
Order By: Relevance
“…Based on the high level of universality in PCR and sequencing aspects, and high species discrimination ability (Figure 2; Figure 3c), we think that ITS should be used as a supplementary barcode on the basis of core barcode matK and rbcL in Chimaphila. The psbA-trnH is an intergenic spacer, both rapidly evolving and variable in length, that has been widely used as a plant barcode, distinguishing among the largest number of plant species for barcoding purposes (Theodoridis et al 2012). In this study, we found that the length of the psbA-trnH is short, ranging from 236 to 245 bp.…”
Section: Discussionmentioning
confidence: 91%
“…Based on the high level of universality in PCR and sequencing aspects, and high species discrimination ability (Figure 2; Figure 3c), we think that ITS should be used as a supplementary barcode on the basis of core barcode matK and rbcL in Chimaphila. The psbA-trnH is an intergenic spacer, both rapidly evolving and variable in length, that has been widely used as a plant barcode, distinguishing among the largest number of plant species for barcoding purposes (Theodoridis et al 2012). In this study, we found that the length of the psbA-trnH is short, ranging from 236 to 245 bp.…”
Section: Discussionmentioning
confidence: 91%
“…; Theodoridis et al . ). Lamium is an interesting object of phylogenetic studies and taxonomic discussion, which among other things concerns infrageneric taxa.…”
Section: Introductionmentioning
confidence: 97%
“…; Theodoridis et al . ). The two‐locus combination of matK and rbcL is recommended as the core plant barcode (CBOL Plant Working Group et al .…”
Section: Introductionmentioning
confidence: 97%
“…are used in the Caribbean for their proposed medicinal properties (Mahabir & Gulliford, 1997). Preservation of indigenous knowledge concerning medical ethno‐botany is a key aspect of bioprospecting with the proviso of accurate species identification (Harvey & Gericke, 2011; Kumar, Sharma, & Chattopadhyay, 2013; Theodoridis et al., 2012). …”
Section: Introductionmentioning
confidence: 99%